2019
DOI: 10.1002/rra.3412
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low‐head dams on fish assemblages in subtropical streams: Context dependence on species category and data type

Abstract: Anthropogenic disturbances may cause cosmopolitan species to replace endemic species, which will alter both the within-community diversities and between-community similarities of stream fish assemblages. In this study, we used data collected from headwater streams within the Xin'an basin, China, to evaluate the effects of low-head dams on the alpha diversity and community similarity of fish assemblages. Our aims were to determine whether the changes in fish diversities and similarities related to damassociated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(39 citation statements)
references
References 33 publications
4
35
0
Order By: Relevance
“…Previous studies have shown that incidence-based dissimilarity may play a crucial role when communities differ mostly in species compositions and are geographically far apart on global or regional scales (Legendre, 2014). However, abundance-based approaches may exhibit higher sensitivity in structuring homogeneous or heterogeneous patterns when species composition may differ primarily in species abundance due to weightings with differentiated abundance in small spatial extents (Cassey et al, 2008;Liu et al, 2019;Dai et al, 2020). Indeed, the population size (i.e., abundance) of the same species may differ substantially across locations, and the number of individuals is not equally distributed across different species in the same locations.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have shown that incidence-based dissimilarity may play a crucial role when communities differ mostly in species compositions and are geographically far apart on global or regional scales (Legendre, 2014). However, abundance-based approaches may exhibit higher sensitivity in structuring homogeneous or heterogeneous patterns when species composition may differ primarily in species abundance due to weightings with differentiated abundance in small spatial extents (Cassey et al, 2008;Liu et al, 2019;Dai et al, 2020). Indeed, the population size (i.e., abundance) of the same species may differ substantially across locations, and the number of individuals is not equally distributed across different species in the same locations.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the population size (i.e., abundance) of the same species may differ substantially across locations, and the number of individuals is not equally distributed across different species in the same locations. Therefore, changes in population abundance can also affect the degree to which communities differ in composition, and a growing body of evidence has shown that the choice of similarity index can influence the magnitude of biological similarity computed (Cassey et al, 2008;Liu et al, 2019). For instance, incidence-based approaches may underestimate the functions of dominant species in biotic homogenization if species abundance data are overlooked (La Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations